2020
DOI: 10.1111/rda.13633
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative ultrasound elastography and biometry of the bitch uterus in the early puerperium after vaginal delivery and caesarean section

Abstract: Elastography is an actual imaging method used to qualitatively and quantitatively evaluate the elastic properties of tissues. The aim of this study was to evaluate and compare uterine tissue biometry and stiffness during post‐partum period in brachycephalic bitches (n = 12) after c‐section (GCS; n = 8) or normal delivery (GNB; n = 4). These animals were evaluated daily by abdominal ultrasound from the day of delivery until the 10th day post‐partum; measuring uterine diameter, myometrial and endometrial thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Various recent veterinary investigations have shown that in dogs, 2-D SWE can be applied for the estimation of stiffness in normal parenchyma of the liver, spleen, kidneys, pancreas, prostate, lymph nodes, submandibular salivary gland, thyroid (12,13), postpartum uterine wall (14), small intestinal wall (15), and thigh muscle (16). Moreover, several studies attempted to compare abnormal lesions of the liver, pancreas, and kidneys with those of normal animals.…”
Section: Introductionmentioning
confidence: 99%
“…Various recent veterinary investigations have shown that in dogs, 2-D SWE can be applied for the estimation of stiffness in normal parenchyma of the liver, spleen, kidneys, pancreas, prostate, lymph nodes, submandibular salivary gland, thyroid (12,13), postpartum uterine wall (14), small intestinal wall (15), and thigh muscle (16). Moreover, several studies attempted to compare abnormal lesions of the liver, pancreas, and kidneys with those of normal animals.…”
Section: Introductionmentioning
confidence: 99%